Involvement of fibroblast growth factor 18 in dedifferentiation of cultured human chondrocytes - Yamaoka, H. (Cell Prolif, 2009)
Objective:  Chondrocytes inevitably decrease production of cartilaginous matrices during long‐term cultures with repeated passaging; this is termed dedifferentiation. To learn more concerning prevention of dedifferentiation, we have focused here on the fibroblast growth factor (FGF) family that influences chondrocyte proliferation or differentiation. Materials and methods:  We have compared gene expression between differentiated cells in passage 3 (P3) and dedifferentiated ones in P8 of human cultured chondrocytes. We also performed ligand administration of the responsive factor or its gene silencing, using small interfering RNA (siRNA). Results:  FGFs 1, 5, 10, 13 and 18 were higher at P8 compared to P3, while FGFs 9 and 14 were lower. Especially, FGF18 showed a 10‐fold increase by P8. Ligand administration of FGF18 in the P3 cells, or its gene silencing using siRNA in the P8 cells, revealed dose‐dependent increase and decrease respectively in type II collagen/type I collagen ratio. Exogenous FGF18 also upregulated expression of transforming growth factor beta (TGF‐β), the anabolic factor of chondrocytes, in P3 chondrocytes, but P8 cells maintained a low level of TGF‐β expression, suggesting a decrease in responsiveness of TGF‐β to FGF18 stimulation in the dedifferentiated chondrocytes. Conclusion:  FGF18 seems to play a role in maintenance of chondrocyte properties, although its expression was rather high in dedifferentiated chondrocytes. Upregulation of FGF18 in dedifferentiated chondrocytes implied that it may be a marker of dedifferentiation.